2022
DOI: 10.1111/jpc.15942
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐organ/disseminated echinococcosis in children: Case series and review of the literature

Abstract: Aim: Echinococcosis with multi-organ/disseminated involvement is rare in childhood. We aimed to evaluate the clinical and laboratory characteristics and prognosis in paediatric patients with echinococcosis having multiorgan/disseminated involvement. Method: We evaluated retrospectively children with echinococcosis with involvement of three or more organs. Results: Thirteen patients were included in the study. The median age was 120 (range 71-189) months. Three (23%) were diagnosed incidentally. Abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[13,21] In a study evaluating the cases with multiple organ involvement, it was reported that the liver, lung and spleen (38.5%) were affected most frequently. [22] In our study, the most involved areas were the right lobe of the liver (75%) and the left lung (58.3%). Cysts <50 mm in size are called small cysts and mm are "giant cysts".…”
Section: Discussionmentioning
confidence: 48%
“…[13,21] In a study evaluating the cases with multiple organ involvement, it was reported that the liver, lung and spleen (38.5%) were affected most frequently. [22] In our study, the most involved areas were the right lobe of the liver (75%) and the left lung (58.3%). Cysts <50 mm in size are called small cysts and mm are "giant cysts".…”
Section: Discussionmentioning
confidence: 48%
“…Limited number of studies have reported renal involvement in pediatric cases. [1][2][3] In the study by Mfingwana 1 and colleagues, only two cases with lung involvement additionally had spleen involvement, while no case of renal involvement was observed. At the same time, In the study by Çay 2 and colleagues, only three cases with lung involvement additionally had renal involvement.…”
Section: Children Lung Echinococcosis Multiorgan Involvementmentioning
confidence: 96%
“…The renal involvement was especially significant in this case. Limited number of studies have reported renal involvement in pediatric cases 1–3 . In the study by Mfingwana 1 and colleagues, only two cases with lung involvement additionally had spleen involvement, while no case of renal involvement was observed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation